Application of Silica Concentration and Planting Methods on the Growth and Yield of TSS Red Onions (Allium ascalonicum L.) - Zerlinda Aqila Gitta Maharani; Ida Retno Moeljani; Djarwatiningsih (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Shallot propagation using seeds or True Shallot Seed (TSS) faces several challenges, including low seedling survivalrates and slow seedling development. This study aims to evaluate the effects of silica concentration and plantingmethods on optimizing the growth and productivity of TSS shallot bulbs. The research was conducted at the UPTDevelopment of Rice and Secondary Crops Seeds in Malang Regency from February to June 2025. The experimentemployed a factorial design arranged as a Completely Randomized Design (CRD) with two factors, resulting ineight treatment combinations, each replicated five times. The first factor was silica concentration at four levels:0 g/L, 12 g/L, 14 g/L, and 16 g/L. The second factor was the planting method, with two levels: direct plantingand soil-block seeding. Observed parameters included seedling growth percentage, plant height, number ofleaves, number of bulbs, wet weight of stover per clump, dry weight of stover per clump, and dry weight of bulbs.The results indicated no significant interaction between silica concentration and planting method on the growthand yield of TSS shallot bulbs. However, the single treatment at 16 g/L silica concentration (S3) significantlyimproved seedling growth percentage and plant height, whereas the direct planting method (T1) yielded higherplant height. These findings suggest that applying a 16 g/L silica concentration and direct planting can enhanceshallot plant growth when propagated from TSS seeds.